Effects and Mechanisms of Radiofrequency Ablation of Renal Sympathetic Nerve on Anti-Hypertension in Canine - Chen,Wei (2017)
Abstract Background: Radiofrequency ablation of renal sympathetic nerve (RDN) shows effective BP reduction in hypertensive patients while the specific mechanisms remain unclear. Objective: We hypothesized that abnormal levels of norepinephrine (NE) and changes in NE-related enzymes and angiotensinconverting enzyme 2 (ACE2), angiotensin (Ang)-(1-7) and Mas receptor mediate the anti-hypertensive effects of RDN. Methods: Mean values of systolic blood pressure (SBP), diastolic blood pressure (DBP) and mean arterial pressure (MAP) were assessed at baseline and follow-up. Plasma and renal norepinephrine (NE) concentrations were determined using highperformance liquid chromatography with electrochemical detection, and levels of NE-related enzyme and ACE2-Ang(1-7)- Mas were measured using real time PCR, Western blot and immunohistochemistry or Elisa in a hypertensive canine model fed with high-fat diet and treated with RDN. The parameters were also determined in a sham group treated with renal arteriography and a control group fed with normal diet. Results: RDN decreased SBP, DBP, MAP, plasma and renal NE. Compared with the sham group, renal tyrosine hydroxylase (TH) expression was lower and renalase expression was higher in the RDN group. Compared with the control group, renal TH and catechol-o-methyl transferase (COMT) were higher and renalase was lower in the sham group. Moreover, renal ACE2, Ang-(1-7) and Mas levels of the RDN group were higher than those of the sham group, which were lower than those of the control group. Conclusion: RDN shows anti-hypertensive effect with reduced NE and activation of ACE2-Ang(1-7)-Mas, indicating that it may contribute to the anti-hypertensive effect of RDN.